The Role of Technology in Anxiety and Depression during the COVID Pandemic - Park, Hyejin (Eximia, 2021)
The purposes of this study were to examine the use of technology tools during COVID-19, determine perceived mental health issues such as anxiety and depression, and identify the relationship between mental health issues and technology use. Secondary data from the Wave 64 survey of the Pew Research Center were used. This study used information from 10,310 participants after excluding those missing data on demographic information. Frequencies and percentages were calculated for categorical variables of age group, gender, race, education, income, marital status, mental health issues, and technology use. Binominal logistic regression was used to test the relationship between perceived mental health status and technology use. Most participants felt nervous, anxious, and depressed and had trouble sleeping a moderate amount of time or all the time. Many respondents (80%) reported using email or messaging services to communicate with others, followed by searching online for information about the coronavirus and using social media to share or post information about coronavirus. Associations between mental health status and use of technologies were mostly statistically significant. The finding shows that people who have used technological tools had fewer mental health issues than who did not use technological tools. It is important to set up the technology infrastructure for present and future crises to address mental health problems.